2017
DOI: 10.22159/ajpcr.2017.v10i11.20389
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of Silver Nanoparticles Using Leaves of Gloriosa Superba and Its Anticancer Properties

Abstract: Objective: We aimed to synthesize the cost effective, one pot and an eco-friendly technique for the green synthesis of silver nanoparticles (AgNPs) using 1 mM of silver nitrate (AgNO 3 ) solution through the aqueous leaf extracts of Gloriosa superba (GS) reducing and capping agent and its anticancer activity.Methods: Synthesis briefly 95 mL of 1 mM AgNO 3 was taken into amber colored conical flask and added 5 mL of aqueous leaf extract of GS (pale brown) and incubated at room temperature in dark condition for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…LnAgNPs had exhibited high antiproliferiative activity over that of the LNELE and commercially available AgNPs. It was found that in a literature, the aqueous leaf extracts of Rhynchosia suaveolens and Gloriosa superba mediated AgNPs showed potent cytotoxic activity at a concentration (IC 50 ) of 4.2 and 61.80±4.27 µg/ml on SK-OV-3 cell lines [6,50]. Further, it was reported that the ethanolic leaf extract of Ocimum basilicum showed cytotoxicity at a concentration of 5 mg/ml within 72 h with an IC 50 value of 0.91±0.11 mg/ml on SK-OV-3 cell lines [51].…”
Section: Characterization Of Agnpsmentioning
confidence: 99%
“…LnAgNPs had exhibited high antiproliferiative activity over that of the LNELE and commercially available AgNPs. It was found that in a literature, the aqueous leaf extracts of Rhynchosia suaveolens and Gloriosa superba mediated AgNPs showed potent cytotoxic activity at a concentration (IC 50 ) of 4.2 and 61.80±4.27 µg/ml on SK-OV-3 cell lines [6,50]. Further, it was reported that the ethanolic leaf extract of Ocimum basilicum showed cytotoxicity at a concentration of 5 mg/ml within 72 h with an IC 50 value of 0.91±0.11 mg/ml on SK-OV-3 cell lines [51].…”
Section: Characterization Of Agnpsmentioning
confidence: 99%